Intervención educativa para fomentar el autocuidado en el adulto mayor - Ortega Pérez, Silvia Graciela (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
Introduction: self-care, personal intentional action, control internal-external factors, compromise life and development. Self-care agency, individual ability, self- care; conditioning factors influence. Objectives: To evaluate the efficacy of an educational nursing intervention to promote self-care in older adults. Material and methods: Quantitative approach with a design, quasi-experimental with pre and post measurements with a single group, prospective, cross-sectional. Non-probabilistic sampling, for convenience, instrument, ASA (Self-Care Agency), Likert scale with only 4 assessments. It was applied in the IMSS Family Medical Unit of Tancítaro Michoacán, obtaining a sample of 30 older adults. Results: the predominant sex was female with 66% (20), of marital status 60% (18) married, the majority is dedicated to housework, 53.3 % (16), of primary school level 66.3 % (19). The disease that prevailed was arterial hypertension with 60% (18), in older adults. The level of self-care agency in the pre- intervention older adult resulted in 60% (18), low self-care agency and only 3.3% (1) high self-care agency. After applying the educational nursing intervention, the results were very favorable, obtaining 60% (18), a high level of self-care agency, and only 3.3% (1), a low level of agency. Discussion: After the intervention, there was an improvement in the level of self-care agency in more than half of the participating population, which is similar to what was reported by Tunga (2019), where he reported that almost the total population increased their self-care agency. self-care. Conclusions: with the results we can verify that there is an efficacy in the nursing educational intervention for the increase of self-care that is the result of the skills and behavior acquired by older adults.

Introducción. Autocuidado, acción intencionada personal, controla factores internos- externos, comprometen la vida y desarrollo. Agencia de autocuidado, capacidad individual, cuidar de sí mismo; influyen factores condicionantes. Objetivo. Evaluar la eficacia de una intervención educativa de enfermería para fomentar el Autocuidado en las personas adultas mayores. Material y método. Enfoque cuantitativo con un diseño, cuasi experimental con mediciones previas y posteriores con un solo grupo, prospectivo y transversal. Muestra no probabilística de 30 Adultos mayores con muestreo por conveniencia; instrumento ASA (Agencia de Autocuidado), escala Likert a solo 4 apreciaciones. Se aplicó en la Unidad Médica Familiar IMSS de Tancítaro Michoacán. Resultados: el sexo que predominó fue el femenino con el 66%, de estado civil 60% casados, la mayoría se dedica a las tareas del hogar (53.3%), de nivel de escolaridad primaria (66.3%). La enfermedad que predominó fue la Hipertensión Arterial con 60%. El nivel de agencia de autocuidado en el adulto mayor pre-intervención dio como resultado 60%, agencia de autocuidado baja tan solo el 3.3% agencia de autocuidado alta. Después de haber aplicado la intervención educativa de enfermería los resultados fueron muy favorables obteniendo un 60%, nivel de agencia de autocuidado alta, y tan solo el 3.3% nivel de agencia baja. Discusión. Posterior a la intervención hubo una mejora del nivel de agencia de autocuidado en más de la mitad de la población participante, lo que es similar a lo reportado por Tunga (2019) donde reportó que casi el total de la población aumentó su agencia de autocuidado Conclusiones. Con los resultados se comprueba que la intervención educativa de enfermería fue eficaz para el aumento del autocuidado debido al incremento en las habilidades y comportamiento adquirido por los adultos mayores.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2022-0720; Gestión dirección y liderazgo; Intervención educativa; Adulto mayor; Agencia de autocuidado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8398